Strategic Approach of Finnish Companies entering the Cameroonian Market: Factors affecting the selection of entry mode. - Admaa, Sixtus (My University, 2012)
There are many challenges for successful entry of Western companies into Cameroon. On the other hand, Cameroon is endowed with natural resources, has a developing economy and companies that are interested in investing in Cameroon should understand the factors that have an effect on the entry mode choice. Therefore the main objective of this thesis was to support Finnish companies to enter the Cameroonian market successfully. An integrated survey of literature in combination with empirical research was employed. The thesis further identifies the major factors that have an effect on the decision of Finnish companies to enter Cameroon. The strategies of two Finnish companies that have entered the Cameroonian market successfully were analysed and it was found that:
Both companies based their market entry strategy into Cameroon on their strengths
They employed wholly owned subsidiary as a mode of entry in to the Cameroonian market.
Furthermore, the factors that have an impact on the selection of an entry mode were classified into two categories. That is internal and external factors. The internal factors are those factors that come from inside the company and the firm has considerable control over the factor while the external factor are those factors that come from the companies’ environment and the company has no influence on the factors but could monitor it.
Keywords: Strategic Management; Market Entry Strategy; Mode of entry; Cameroon Institutional Environment.; fi=Master's Degree Programme in Industrial Management|